Determinar la metodología para el diseño mecánico de redes eléctricas de media tensión. - Loayza Aguilar, Cristhian Ivan (2022)
This research work consists of proposing a methodology to carry out the mechanical calculation of conductors in the design of medium voltage electrical networks, the procedures considered are based on the norms and bibliography of the “Empresa Eléctrica Regional del Sur SA” (EERSA), “Ministerio de Electricidad y Energía Renovable” (MEER), “Corporación Nacional de Electricidad” (CNEL), “Empresa Pública Municipal de Telecomunicaciones, Agua, Potable, Alcantarillado y Saneamiento” (ETAPA-EP), among others. The developed study summarizes the collection of information from different mechanical calculation processes in the design of electrical networks, being able to formulate an integral method. To carry out the present work and verify the effectiveness of the applied methodology, a case study was carried out, where the information provided by the EERSSA related to the profile of a Yanacocha-Virgenpamba primary feeder in the Loja canton was used. Applying the proposed calculation methodology, the type of conductor was selected, the useful wind exertion on the pole, and the mechanical exertion parameters were determined. For each of the states and in different section, the mechanical tension at different temperatures and the safety distance between conductors were calculated. Each of the variables of the change of state equation is described and the regulator section and the electrical wiring tables are calculated. Key Words: worknets, transmission, tension, status, methodology.